2014
DOI: 10.1021/ja506074a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Liquid Crystals as a Versatile and Tunable Alignment Medium for the Measurement of Residual Dipolar Couplings in Organic Solvents

Abstract: Residual dipolar couplings (RDCs) have proven to be an invaluable anisotropic NMR parameter for the structural elucidation of complex biopolymers and organic molecules. However, a remaining bottleneck limiting its wider use by organic and natural product chemists is the lack of a range of easily applicable aligning media for diverse organic solvents. In this study, graphene oxide (GO) liquid crystals (LCs) were developed to induce partial orientation of organic molecules to allow RDC measurements. These LCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…The viscosity of the SWNTs solution in 102% H 2 SO 4 plotted against GO and improve the dispersion and stability of the GO in a polar solvent without any additive [71][72][73].…”
Section: Liquid Crystalline Spinning Of Cntsmentioning
confidence: 99%
“…The viscosity of the SWNTs solution in 102% H 2 SO 4 plotted against GO and improve the dispersion and stability of the GO in a polar solvent without any additive [71][72][73].…”
Section: Liquid Crystalline Spinning Of Cntsmentioning
confidence: 99%
“…Residual dipolar couplings have proven to be an invaluable anisotropic (NMR) parameter for the structural elucidation of complex biopolymers and organic molecules. Lei et al demonstrated that GO LCs can act as versatile and tunable alignment medium for the measurement of residual dipolar couplings in organic solvents [123]. The LCs were found to be maintainable at very low concentrations and to be remarkably stable and broadly compatible with both aqueous and organic solvents.…”
Section: Liquid Crystalline Graphene Derivativesmentioning
confidence: 99%
“…Cross‐linked polystyrene (PS), poly (vinylacetate) (PVAc), cross‐linked poly (dimethylsiloxane) (PDMS), poly (methyl methacrylate) (PMMA), and the cross‐linked poly (ethylene oxide) (PEO) are the gel‐based alignment media that have been developed in recent years . The liquid crystals include the high‐molecular weight homopolypeptides represented by poly‐ γ ‐benzyl‐L/D‐glutamate (PBLG/PBDG), poly‐γ‐ethyl‐L/D‐glutamate (PELG/PEDG), poly‐ε‐carboxybenzoyl‐L/D‐lysine (PCBLL/PCBDL), and helically chiral polymers such as polyguanidines exemplified by poly‐( N ‐methyl‐ N ′‐(( R )‐1‐phenylethyl)guanidine(( R )‐PPEMG), polyarylacetylenes, polyarylisocyanides, polyisocyanopeptides, as well as carbon‐based graphene oxide (GO) sheets …”
Section: Introductionmentioning
confidence: 99%